A Review About Toxoplasmosis on Animals and Humans - Iskandar, Tolibin (Indonesian Bulletin of Animal and Veterinary Sciences, 1999)
Toxoplasmosis, a zoonotic infectious disease caused by Toxoplasma gondii, is reported to be endemic throughout most of the Indonesian archipelago . The prevalence rates of 24-61% in goats, 10-40% in cats, 28% in pigs, 43% in sheep, 36% in cattle, 27% in buffalo, 20% in chickens, 6% in ducks, 10% in dogs and 14-82% in human were reported in Indonesia. The disease causes abortion in pregnant women. The importance of toxoplasmosis in Indonesia; the aspects of etiology, clinical signs, pathology, transmission and control measures are discussed in this paper. Key words: Toxoplasmosis, animals, humans